Human Toxocariosis in patients with ocular damage - Espinoza, Yrma (2003)
Objective: To determine human toxocariosis prevalence in subjects presenting suspicious ocular symptoms. Material and methods: Subjects with symptoms and suspicion of intraocular toxocariosis damage attended at various Lima hospitals ophtalmology services were studied. Blood samples were obtained and Toxocara serology by ELISA technique was done, along with leukocyte counts. An epidemiological questionnaire was also applied to identify behaviors associated to infection risk. Results: Forty-five persons were studied, 19 male and 26 female, 55,6% were reactive by ELISA test. No differences in sex and serology results were observed; among participants between 15 and 45 years old, 63% were reactive. There were no significant differences in the epidemiological factors studied. No association between eosinophilia and serology was observed. Conclusions: Human infection by Toxocara is frequent in people with clinical symptoms and affects mainly to productive age population. We suggest active search for the infection in order to prevent complications.